1973
DOI: 10.1159/000231070
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Allergic Reactions by Cromoglycate and by a New Series of Compounds (AH 6556, AH 7079 and AH 7725)

Abstract: (1) A new series of anti-allergic drugs (AH 6556, AH 7079 and AH 7725) were shown to inhibit immediate-type allergy. They act by inhibiting release of pharmacological mediators, and they do not possess any bronchodilator activity. (2) Inhibition of allergic reactions was shown experimentally in a wide range of in vitro test models, and supports the findings in the preliminary in vivo studies in experimental animals. (2) The experimental evidence suggests that these compounds have some qualitative and quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2

Year Published

1975
1975
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 7 publications
(7 reference statements)
1
5
2
Order By: Relevance
“…74,917 was administered intradermally (Table 2). Neither compound was active when given intravenously, which conflicts with the finding of Orr, Hall, Gwilliam & Cox (1971) (Assem, 1973;Taylor & Roitt, 1973) have shown that DSCG inhibits certain allergic reactions in the guinea-pig, no consistent or significant inhibitory activity was found in the present work at intravenous doses up to 50 mg/kg. In contrast, I.C.I.…”
Section: Ol_contrasting
confidence: 99%
“…74,917 was administered intradermally (Table 2). Neither compound was active when given intravenously, which conflicts with the finding of Orr, Hall, Gwilliam & Cox (1971) (Assem, 1973;Taylor & Roitt, 1973) have shown that DSCG inhibits certain allergic reactions in the guinea-pig, no consistent or significant inhibitory activity was found in the present work at intravenous doses up to 50 mg/kg. In contrast, I.C.I.…”
Section: Ol_contrasting
confidence: 99%
“…In this context, the concentrations of DSCG used in vitro, 100 and 1,000 /tg/ml, are much greater than the plasma concentration of DSCG (maximum 12.1 ng/ml, mean 9,2 ng/ml) in asthmatic patients re corded after a single inhalation dose of 20 mg [W alker et al, 1972], The average plasma half-life of DSCG was 81 min in their study. These findings confirm and extend a report that lymphocyte transformation re sponse to PPD in two patients was not affected by DSCG [Assem, 1973]. Thus, in those patients whose allergic respiratory disease is pre vented by DSCG, delayed hypersensitivity may not be important in the pathogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…A and for DSCG in vitro depend upon time of compound addition with respect to immunological challenge, level of release (large releases cannot be inhibited) and con centration of inhibitor. Since DSCG often shows a biphasic dose response and often enhances release at very low DSCG concentrations instead of inhibiting release, it is very difficult to draw definitive conclusions or meaningful dose-response curves from rat mast cell experiments [2,11,12). Comp.…”
Section: Discussionmentioning
confidence: 99%